Chomsky & Large Language Models: A response to Piantadosi (2023) - Jiménez Sennrich, Diego A. (2024)
In a recent article, Steven T. Piantadosi proposes that «Modern language models refute Chomsky’s approach to language». The present paper intends to show that Piantadosi’s argument is based on a misunderstanding of both Chomsky’s approach to language and, more broadly, language acquisition restrictions serious linguistic theories ought to commit to. As a result, it is shown that under rational theory choice considerations Chomsky’s approach trumps Piantadosi’s.